General Hospitals with High-Tech Medical Equipment and Patient Experience - Se Min Oh MPH; Jun Su Park BPH; Bomgyeol Kim PHD; Suk-Yong Jang MD, PHD; Sang Gyu Lee MD, PHD; Tae Hyun Kim PHD (Journal of Patient Experience)
This study investigates the relationship between the retention of high-tech medical equipment in medical institutions in South Korea and patient experience evaluation outcomes. Data were sourced from the third Patient Experience Assessment conducted by the Health Insurance Review and Assessment Service (HIRA), a South Korean agency, and HIRA's 2021 data on medical equipment. A total of 320 institutions equipped with CT, MRI, and PET scans or only CT and MRI were analyzed. The dependent variable was the average score across six patient experience dimensions: overall, nurses, doctors, medication and treatment, hospital environment, and guarantee of patient rights. Multiple regression analysis revealed that institutions with CT, MRI, and PET scans scored higher in-patient experience, particularly in the overall dimension (2.15 points), hospital environment (2.22 points), patient rights (1.77 points), and doctors (1.54 points). These findings suggest that high-tech medical equipment positively influences patient satisfaction with care quality. Medical institutions should consider these factors when aiming to enhance patient experience.